Ketimpangan Sosial dalam Cerpen “Gerobak” Karya Seno Gumira Ajidarma (Teori Interaksi Sosial George Simmel) - Anisa Br Pelawi; Santa Elvira Nainggolan; Shela Jenari Marbun (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Short stories as a form of literary works often raise social issues, show the dynamics of social interaction, and describe various conflicts that arise in people's lives. One of them is the short story “Gerobak” by Seno Gumira Ajidarma which will be studied using George Simmel's Social Interaction theory. This short story highlights the social inequality between the rich and the poor and creates instability in the interaction of society. This research aims to analyse how social interaction and social conflict in the short story can be studied using George Simmel's theory. This research uses descriptive qualitative research method. The object of this research is the short story "Gerobak" by Seno Gumira Ajidarma. The methods used in data collection are literature study and data recording. The data in this research are primary data and secondary data. Data analysis uses data identification, data classification and data interpretation. Finally, the results of the analysis are poured into critical writing with sub-chapters and short story fragments.